Chinese in Ilocos, 1950s-1960s. - Reynolds, Hubert, 1914-1993; Reynolds, Harriet R., 1910- (Manila, Philippines : Kaisa Para sa Kaunlaran, 1998)
pt. 1. Chinese acculturation in Ilocos: economic, political, religious/ I. Hubert, Reynolds - - pt. 2. Continuity and change in the family in Ilocos/ Harriet R. Reynolds
Revision of the authors' theses. Includes bibliographical references (p. (290]-306)
Keywords: Chinese -- Cultural assimilation -- Philippines -- Ilocos; Family -- Philippines -- Ilocos; Philippines -- Ethnic relations